NEW VARIETIES AND HETEROSIS HYBRIDS OF COLE CROPS OF VNIISSOK'S BREEDING - L. L. Bondareva (Овощи России)
The description of new varieties and F1 hybrids of different species and subspecies of cole crops of VNIISSOK's breeding are represented